The Influence of Brand Trust and Customer Experience on Customer Loyalty in Life Insurance Companies - U-Thairatana, Pichaya; Upariputti, Thanyamas; Chiyachantana, Chirasak (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This research aimed to achieve two objectives: (1) to investigate the influence of brand trust and customer experience on life insurance company loyalty, and (2) to examine the influence of brand trust on customer experience. Data were collected from 240 samples of repeat customers who had purchased more than one policy from the same life insurance company, using convenience sampling. Statistical analyses included frequency, percentage, confirmatory factor analysis (CFA), and path analysis using structural equation modeling (SEM). The findings revealed that (1) life insurance company loyalty was directly and statistically significantly influenced by brand trust (DE=0.56) and customer experience (DE=0.49), with a predictive power of 90%. (2) Customer experience was directly and statistically significantly influenced by brand trust (DE=0.83), with a predictive power of 61%. Based on the confirmatory factor analysis with the highest factor loadings, brand trust was primarily weighted by reliability (REL=0.54), customer experience by social experience (SOC=0.51), and life insurance company loyalty by repurchase intention (REI=0.48). Article history: Received 8 February 2025 Revised 19 April 2025 Accepted 21 April 2025 SIMILARITY INDEX = 0.84 %